Pengaruh Kredibilitas Konten Tiktok, Brand Trust, dan Brand Image Terhadap Minat Beli Followers Akun @by.diaraofficial - Ulkhusna, Dewi Cantika Hikmah; Giningroem, Dewi Sri Woelandari Pantjolo; Puspitorini, Ferawaty (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze the influence of TikTok content credibility, brand trust, and brand image on the purchase intention of @by.diaraofficial followers. The background of this research is the increasing use of social media as a promotional tool, particularly TikTok, which is considered effective in shaping consumer perception and decision-making. This research employs a quantitative approach using a survey method by distributing questionnaires to followers of the @by.diaraofficial account. The sampling technique applied is purposive sampling, and the sample size is determined using the Lemeshow formula. The collected data were analyzed using multiple linear regression analysis with the help of SPSS software. The results of this study are expected to contribute to digital marketing strategies, especially in building brand image and consumer trust through social media content.